Exploring Students' Engagement in Learning English Vocabulary through Wordwall Media for Secondary Level - Rananur Alfiah; Made Hery Santosa; Putu Indra Kusuma (Publikasi Indonesia, 2024)
The use of Wordwall is essential for learning English vocabulary as an interactive and effective medium. Wordwall media can help students increase their engagement in learning vocabulary. The purpose of this research is to investigate students' perceptions of how engaged students are in learning English vocabulary using Wordwall. This research uses a qualitative approach with a case study design. This research was carried out in one of the junior high schools located in Bima NTB, especially in grade eight. Then, three students were selected purposively to participate in the research to represent the population based on recommendations from English teachers with the criteria of being low to active in learning English. The data was collected through documentation and interviews. In the documentation, students are asked to do several activities in Wordwall regarding learning material for around 20 minutes. Then, students are asked to write about 10 new vocabularies based on the Wordwall they learned. Furthermore, interviews in the form of semi-structured interviews are related to three main aspects of student engagement by Fredricks and McColskey (2012) such as cognitive, behavioral, and emotional engagement. The findings in this research are that using Wordwall can help the students enrich their vocabulary (cognitive), students provide positive reactions during learning (emotional), and students actively participate during the learning process by using Wordwall (behavior).